Biomechanical differences of general jumps and volleyball specific jumps on hard floor and two sand types - Frese, C. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Beachvolleyball is one of the most successful competitive sports in germany besides indoor. Even though kinematic and kinetic differences between indoor and sand condition for different jump types could be proven (1,2), the influence of sand type on those jumps and on injury potential is unknown (3,4). Hence, the aim of this study is to investigate biomechanical variables for the hard floor condition and two sand types differing in degree of hardness.